P271 Underlying disease and causative microorganisms of recurrent pneumonia in children: 13-year study in a university hospital. (6th June 2017) - Özdemir, Halil; Yildiz, Nihan; Kocabaş, Bilge Aldemir; Erat, Tuğba; Yahşi, Aysun; Doğu, Figen; Tutar, Ercan; Ince, Erdal; Çiftçi, Ergin
Abstract : Background and aims: Pneumonia is the most important cause of death in children in many countries. The use of inappropriate antibiotics in the treatment of pneumonia is associated with multi drug resistant microorganisms that lead to increased morbidity and mortality. Therefore, the causative microorganism should be detected for avoidence of unnecessary antibiotic usage. Underlying diseases are predisposing factors for recurrent pneumonia. The choice of pneumonia treatment should be based on causative microorganisms and underlying diseases. In this study we aimed to evaluate the frequency of recurrent pneumonia and underlying disease in hospitalised children, to identify the distribution of causative microorganisms and to compare our data with previous studies. Methods: Between January 2003 and December 2015 children hospitalised due to pneumonia were retrospectively owerviewed. The patients who met criteria for recurrent pneumonia were included in this study. Demographic, clinical, laboratory and imaging results were collacted from the data system. Results: During 13 years, 129 (9.2%) hospitalised children met criteria of recurrent pneumonia. Underlying diseases were detected in 95 (73.6%) patients. Rhinovirus, adenovirus and respiratory synstial virus were the most frequent causative agents. Conclusion: The majority of patients who were hospitalised due to recurrent pneumonia had an underlying disease. The most common cause was aspiration syndrome and viruses were leading causative agents for recurrent pneumonia. As a result; It should kept in mind that viruses can be commonly seen in recurrent pneumonia. Appropriate treatment choice should be made according to the underlying disease, clinical condition, laboratory and radiological data of the patient.